2011
DOI: 10.1007/s10120-011-0078-5
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Taxotere and cisplatin with continuous-infusion 5-fluoruracil for the treatment of advanced gastric and esophageal cancer: a prospective, observational, single-institution experience

Abstract: The combination of Taxotere (docetaxel), cisplatin, and prolonged-infusion 5-fluorouracil (5-FU) has emerged as an active treatment for advanced gastric cancer. However, the regimen proposed by van Cutsem et al. (J Clin Oncol 24:4991-7, 2006) is associated with significant toxicity and therefore alternative schedules are needed. In the present study, patients with advanced gastric or esophageal cancer received Taxotere 35 mg/m 2 and cisplatin 25 mg/m 2 on day 1, followed by 5-FU 180 mg/m 2 / day as a 7-day pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Cisplatin (DDP) is the frequently-used chemotherapeutic agent shown to improve survival in patients with ESCC, as established by randomized controlled trials and therefore approved by the Food and Drug Administration for this use [45-48]. Resistance to chemotherapy, especially to DDP, has presented itself as a major obstacle in treatment of advanced ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin (DDP) is the frequently-used chemotherapeutic agent shown to improve survival in patients with ESCC, as established by randomized controlled trials and therefore approved by the Food and Drug Administration for this use [45-48]. Resistance to chemotherapy, especially to DDP, has presented itself as a major obstacle in treatment of advanced ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported here showed that ILK silencing could reverse the drug resistance of SGC7901/ DDP, a human gastric carcinoma cell lines with multi-drug resistance. A panel of molecules associated with multiple drug resistance and tumorigenicity were solidly regulated Cisplatin is a major chemotherapy drug in gastric carcinoma treatment (Piacentini et al, 2012). Drug resistance is a common problem faced in gastric carcinoma care and therefore new treatment strategies are in urgent.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the effect and mechanism of ANXA2 on MDR in GC, we successfully established a DDP resistant cell line SGC7901/DDP after continual exposure of SGC7901 to cisplatin, a major chemotherapy drug in gastric carcinoma treatment [30].The results showed that the resistance index was 23.4. The establishment of SGC7901/DDP cells has provided a powerful tool for further study of the effect and mechanism of ANXA2 on MDR.…”
Section: Discussionmentioning
confidence: 99%